A new era for Australian astronomy. Issue 3 (1st June 2018) - Watson, Fred; Urquhart, Jane
Abstract : Fred Watson and Jane Urquhart explain what is happening to the AAO. Abstract : It's all change for the Australian Astronomical Observatory – Fred Watson and Jane Urquhart explain what is happening to this astronomical powerhouse.